Нові та рідкісні для України види родини Coprinaceae. 2. Рід Coprinus (секція Pseudocoprinus) - Придюк, М.П. (Український ботанічний журнал, 2014)
Сообщается о находках новых и редких для Украины представителей секции Pseudocoprinus (Kühner) P.D. Orton et Watling рода Coprinus Pers. Впервые для Украины приводится Coprinus sclerocystidiosus M. Lange et A.H. Sm., а для C. auricomus Pat., C. callinus M. Lange et A.H. Sm., C. impatiens (Fr.: Fr.) Quél. и C. silvaticus Peck зарегистрированы новые местонахождения. Даны диагнозы этих видов, локалитеты, информация об общем распространении и оригинальные иллюстрации. The data about finds of some new and rare for Ukraine representatives of the section Pseudocoprinus (Kühner) P.D. Orton et Watling of the genus Coprinus Pers. are reported. Coprinus sclerocystidiosus M. Lange et A.H. Sm. is recorded for the first time for Ukraine, and new localities for C. auricomus Pat., C. callinus M. Lange et A.H. Sm., C. impatiens (Fr.: Fr.) Quél. and C. silvaticus Peck are registered. Their descriptions, localities, data on general distribution and original drawings are given.